1992
DOI: 10.1136/pgmj.68.803.735
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in adult polycystic kidney disease

Abstract: Summary:In order to assess the incidence of acute cerebrovascular events, 142 patients with adult polycystic kidney disease were retrospectively reviewed. Fourteen patients (9.8%) had 19 cerebral attacks. Six patients (4.2%) had intracranial haemorrhage attacks (three ruptured intracranial aneurysms and three cerebral haemorrhages). Ischaemic events occurred in nine patients (five cerebral infarctions and four transient ischaemic attacks). Patients with ischaemic attacks had a better outcome than patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…SAH in our study occurred at an average age of 39 years, which is consistent with that previously reported [2,15,16]. In a study of 258 ADPKD patients with SAH, the mean age was 41 years in ADPKD cases and 53 years in non-ADPKD cases [15].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…SAH in our study occurred at an average age of 39 years, which is consistent with that previously reported [2,15,16]. In a study of 258 ADPKD patients with SAH, the mean age was 41 years in ADPKD cases and 53 years in non-ADPKD cases [15].…”
Section: Discussionsupporting
confidence: 81%
“…The reported incidences of SAH and ICH in ADPKD patients are similar [2,3,16]. In contrast, the incidence of ICH is usually higher than that of SAH in the general population [19].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[33][34][35] ICA ruptures: Rupture of aneurysms is the most serious complication in ADPKD and may account for 7% to 13% of deaths in ADPKD. 36 The average age of ICA rupture was 49.2 years in our study, higher than 41 years reported by Rivera et al 37 Only two of the subjects with ruptured ICA were diagnosed clinically. This might have been due to the sparing use of angiographic technology in our study owing to technicalities and costs.…”
Section: Extra-renal Presentationsmentioning
confidence: 46%